Rates and outcomes of total knee replacement for rheumatoid arthritis compared to osteoarthritis. Issue 3 (15th February 2019) - Mooney, Luke; Lewis, Peter L.; Campbell, David G.; Peng, Yi; Hatton, Alesha
Abstract : Background: Total knee replacement (TKR) has been shown to perform differently in patients with rheumatoid arthritis (RA) when compared to osteoarthritis (OA). In this study, we compare the survivorship between these two groups and examine patient and prosthesis factors that impact the revision rate. Methods: All RA and OA patients undergoing TKR in Australia from 1 September 1999 to 31 December 2016 were included. Revision rates were assessed using Kaplan–Meier estimates of survivorship. The cumulative percent revision analysed age, gender, prosthesis constraint and revision for infection. Results: There were 541 744 TKR procedures performed including 7542 patients with RA. RA declined as the primary diagnosis from 2.4% of all TKR in 2003 to 0.9% in 2016. Male sex was an independent revision risk in RA patients (hazard ratio (HR) = 1.66, P < 0.001) and OA patients (3.5 years+: HR = 1.09 (1.04–1.15), P < 0.001). Male RA patients had a higher revision rate for infection than females (HR = 3.14, P < 0.001). Females with RA had a lower cumulative percent revision compared to OA females, but males showed no difference between diagnoses. Revision in RA patients was not influenced by age. Compared to OA, RA patients had a decreased revision rate for those aged <65 years, but not for patients aged ≥65 years. Conclusion: The rate of revision after TKR in RA patients is lower than those with OA, but patients with RA are at increased risk of infection, particularly the male group. Prosthesis constraint had no influence on revision rate. Mortality in those undergoing TKR with RA was higher than in those with OA. Abstract : This study shows that the use of primary total knee replacement (TKR) for rheumatoid arthritis (RA) is declining. The rate of revision after TKR in RA patients is lower than those with osteoarthritis, but patients with RA are at increased risk of infection, particularly the male group. For patients diagnosed with RA undergoing TKR, the rate of revision varies with gender but not with age.